Ribbon of Peace Banners in Front of Sisk Federal Courthouse - Watkins, Howard::::::::: (1985)
Close up of Watkins Family banner saying "Peace" on green cloth with a red rose, butterflies, daisies and a rainbow; Carol Fischer in pink top